Investigating the mediating role of self-efficacy on work stress and job insecurity among Indonesian startup employees - Jefta Harlianto; Rudi; Aga Qurota Ayun Hakim; Steven Lo (Problems and Perspectives in Management, 2025)
Type of the article: Research Article AbstractThe wave of layoffs in Indonesia’s startups has increased employees’ concerns about job insecurity, raising the need for a deeper understanding of its determinants. This study examines the associations between work stress, self-efficacy, and job insecurity in Indonesia’s startup ecosystem. Specifically, it investigates direct and indirect effects of work stress on job insecurity through self-efficacy. Data were collected from 262 digital startup employees in Jakarta using an online survey at the beginning of 2024 and analyzed using covariance-based structural equation modeling with LISREL software. The findings suggest that work stress does not directly influence job insecurity (T-value of 0.79 < 1.967), indicating that startup employees may perceive stress as a regular aspect of their dynamic and high-pressure work environment. However, work stress significantly and positively impacts self-efficacy (T-value of 11.32> 1.967), implying that stress can enhance employees’ confidence in their abilities when managed effectively. Self-efficacy has a significant and positive effect on job insecurity (T-value of 9.98 > 1.967), highlighting its pivotal role in shaping perceptions of job stability. Furthermore, work stress indirectly influences job insecurity through self-efficacy (Indirect effect 0.7392 > direct effect 0.045), emphasizing the mediating role of self-belief in mitigating the adverse effects of workplace stress. The findings emphasize the importance of fostering self-efficacy through supportive management, training programs, and clear communication to lessen job insecurity and promote resilience. These insights provide practical implications for enhancing employee well-being and organizational sustainability in the rapidly evolving startup environment.